Type-II Band Alignment and Tunable Optical Absorption in MoSSe/InS van der Waals Heterostructure - Yuan, X. B.; Guo, Y. H.; Wang, J. L.; Hu, G. C.; Ren, J. F.; Zhao, X. W. (Frontiers in Chemistry, 2022)
In this work, we study the electronic structure, the effective mass, and the optical properties of the MoSSe/InS van der Waals heterostructures (vdWHs) by first-principles calculations. The results indicate that the MoSSe/InS vdWH is an indirect band gap semiconductor and has type-Ⅱ band alignment in which the electrons and holes located at the InS and the MoSSe side, respectively. The band edge position, the band gap and the optical absorption of the MoSSe/InS vdWH can be tuned when biaxial strains are applied. In addition, compared with MoSSe and InS monolayers, the optical absorption of the MoSSe/InS vdWH is improved both in the visible and the ultraviolet regions. These findings indicate that the MoSSe/InS vdWHs have potential applications in optoelectronic devices.